Clay-Supported Copper Nitrate (Claycop): A Mild Reagent for the Selective Nitration of Aromatic Olefins - Begari, Eeshwaraiah; Singh, Chandani; Nookaraju, U.; Kumar, Pradeep (Synlett, 2014)
A straightforward and highly selective method has been developed for the nitration of a wide variety of aromatic and aliphatic olefins by using a clay-supported copper nitrate (Claycop) and a catalytic amount of (2,2,6,6-tetramethylpiperidin-1-yl)oxyl, an inexpensive and mild reagent system. High conversions and exclusive E-selectivity, together with the environmentally benign nature of the Claycop reagent, make this a green method and an attractive alternative to established methods.
Keywords: nitrations; alkenes